Inventory Of Randang Recipes In Nagari Tepi Selo - Riva Septia Ningsih; Lucy Fridayati (Universitas Negeri Padang, 2020)
This research was motivated by the high curiosity of researchers to obtain accurate knowledge about randang in Nagari Tepi Selo. There is no book that explains the various recipes of randang and the processing of randang in this Nagari. This study aims to make an inventory of the kinds of randang recipes that include ingredients and spices, equipment and processing processes in this Nagari. This type of research is qualitative. Data collection techniques by means of observation, interviews and documentation. Data analysis used in the field is reduction, display, conclusion and verification. The results of this study were the various recipes of randang in Nagari Tepi Selo, namely beef randang, chicken, eggs and jackfruit. Generally, the main ingredient used is beef using wet and dry seasonings. The tools used are cloth sieve, comm, millstone cutting board and blender, stale cauldron, stale sanduak and stove, samba plate. The process of making randang in Jorong Kota, Kaja and Tangah Padang uses a furnace with different spices processing